Ansiedade social e assertividade em estudantes do ensino superior - NEIVA, Yuri Pacheco (2021)
Anxiety is physiological, emotional, and behavioural adaptive reaction which every individual experience in life. In social situations, it is possible to feel anxiety, it is called social anxiety. The scientific literature does not present consensus in regard of the causality of the construct. Still, individuals with social anxiety may present deficits on social skills repertoire, especially in assertiveness, which can impact behaviour on different contexts, inclu. The university environment demands control of anxiety responses and an elaborate repertoire of Social Skills - SK, since academics need to express opinion on class, perform group activities, present seminars, and interact with authorities. Thus, this study aims to analyse the relation between social anxiety and assertiveness. The data was collected using the Individual Characterization Protocol and another three instruments, Assertive Skills Inventory (ASI), the Social Anxiety Test for University students and the Academic Experiences Questionnaire – abbreviated version. The data was virtually applied as an online form in 270 participants with mean age of 24 years (SD = 5,93), from several regions of Brazil, 72,59% were from the northeast region. The data was analysed with the Jasp software version 0.14. The psychometric properties of the ASI were done to ensure that the instrument was capable of measuring assertiveness on university students. Satisfactory adjustment indexes were found for the discomfort indicator (χ2/df = 3,78, CFI = .916, TLI = .903, RMSEA = .102, SRMR = .108) and frequency (χ2/df = 1,81, CFI = .936, TLI = .925, RMSEA = .055, SRMR = .77). The hypothesis that exists a correlation between the variables were confirmed by the Pearson Correlation, with significative relations, ranging from weak to moderate (-.16 to -.51). The mediation analyses allowed to identify that assertiveness can reduce the impact of social skills on adaption to the university. The data strengthens the need of intervation amongst the sample studied and aplify the possibilities of investigation in the practical theoretical field